2012
DOI: 10.1002/14651858.cd009234.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pain management for women in labour: an overview of systematic reviews

Abstract: Background The pain that women experience during labour is a ected by multiple physiological and psychosocial factors and its intensity can vary greatly. Most women in labour require pain relief. Pain management strategies include non-pharmacological interventions (that aim to help women cope with pain in labour) and pharmacological interventions (that aim to relieve the pain of labour). Objectives To summarise the evidence from Cochrane systematic reviews on the e icacy and safety of non-pharmacological and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
218
2
25

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(249 citation statements)
references
References 168 publications
4
218
2
25
Order By: Relevance
“…Childbirth is associated with one of the most severe pains experienced by females over their lifetime (1). The sympathetic nervous system responds to the pain via increasing the release of catecholamines to the blood flow, which can adversely affect the activity of uterus and uteroplacental circulation, and result in maternal and fetal complications (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childbirth is associated with one of the most severe pains experienced by females over their lifetime (1). The sympathetic nervous system responds to the pain via increasing the release of catecholamines to the blood flow, which can adversely affect the activity of uterus and uteroplacental circulation, and result in maternal and fetal complications (2).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are used to reduce pain and anxiety during labor (1). However, analgesics and anesthetics should not be used as the first choice for the pain management, due to their potential side effects on mother and fetus (5).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of opioids on labor pain has been described as modest at best; however, the sedative effects may benefi t some women. A recent overview of systematic reviews found insufficient evidence of effective labor analgesia with opioids [ 21 ]. Maternal side-effects of opioid analgesia include nausea, vomiting, sedation, dysphoria, pruritis, amnesia in high doses and respiratory depression.…”
Section: Opioidsmentioning
confidence: 99%
“…Many other practices are used during labor to help women manage their pain and to promote the progress of labor; these include epidural analgesia, nitrous oxide, and immersion in water (Anim-Somuah et al, 2011;Cluett and Burns, 2009;Jones et al, 2012;Lawrence et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some of them can have adverse side effects (such as nausea or vomiting with nitrous oxide) or even affect maternal outcome (e.g., there is an increased risk of assisted vaginal birth with epidural analgesia) (Anim-Somuah et al, 2011;Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%